346 THE POTENTIATION OF NOISE-INDUCED HEARING LOSS BY JP-8 JET FUEL IN RATS. Issue 1 (1st January 2007) - Moon, P.; Gearhart, C.; Fulton, S.; Pouyatos, B.; Nelson-Miller, A.; Fechter, L.
Abstract : Purpose of Study: JP-8 jet fuel is believed to induce hearing loss particularly in individuals exposed to noise. However, the amount of JP-8 jet fuel needed to cause this effect has not yet been exhibited. JP-8 jet fuel contains two organic solvents, toluene and ethyl benzene, which have been found to cause hearing impairment. In this present study, a toluene and ethyl benzene mixture in the same ratio found in JP-8 jet fuel was used to enable us to estimate the dosage of JP-8 jet fuel that might be needed to cause noise-induced hearing loss in rats. Methods Used: Subjects were placed in different combinations of noise and toluene + ethyl benzene exposure groups. Furthermore, one set of groups was exposed to the stated conditions for 5 days, whereas another was treated for 10 days. Three methods to determine auditory function (distortion product otoacoustic emissions, compound action potentials, and histological analysis) were used. Summary of Results: The results suggest that the groups exposed to noise + solvents developed hearing impairment, particularly in the midfrequency range. Histologic analysis of the cochlea also revealed outer hair cell loss correlating to the midfrequency range. However, it is important to note that the groups treated with noise or solvents alone showed no significant permanent disruption of auditory function. Conclusion: When JP-8 jet fuel is present simultaneously with noise, the loss of hearing is greater than what would be expected from just the separate additive effects of noise and JP-8 jet fuel. This study was supported in part by Loma Linda University School of Medicine and VA grant C-3575R.